2013
DOI: 10.1111/eci.12102
|View full text |Cite
|
Sign up to set email alerts
|

Circadian rhythms in acute intermittent porphyria – a pilot study

Abstract: Acute intermittent porphyria (AIP) is an inherited disorder of heme synthesis wherein a partial deficiency of porphobilinogen [PBG] deaminase [PBGD], with other factors may give rise to biochemical and clinical manifestations of disease. The biochemical hallmarks of active AIP are relative hepatic heme deficiency and uncontrolled up-regulation of hepatic 5-aminolevulinic acid [ALA] synthase-1 [ALAS1] with overproduction of ALA and PBG. The treatment of choice is intravenous heme, which restores the deficient r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
1
5
0
Order By: Relevance
“…The overall decrease of corticosteroid excretion reported here is in agreement with the observations of Larion et al [ 13 ] who found a decrease of cortisol in plasma in 3 AIP women with active disease. Moreover, we found a negative correlation between heme precursor concentrations in urine and most of the cortisol metabolites.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…The overall decrease of corticosteroid excretion reported here is in agreement with the observations of Larion et al [ 13 ] who found a decrease of cortisol in plasma in 3 AIP women with active disease. Moreover, we found a negative correlation between heme precursor concentrations in urine and most of the cortisol metabolites.…”
Section: Discussionsupporting
confidence: 93%
“…A pilot study by Larion et al [ 13 ] studied circadian rhythms in AIP and found a decrease of plasma cortisol in patients with biochemically active disease. These findings suggested that in addition to hepatic involvement, AIP may be associated with hormonal disturbances originating in the adrenal gland.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to anxiety, the sleep disturbance model also did not have many clinical features associated with the domain. Disturbances in circadian rhythms of AIP patients has been previously shown 34 and the recently completed EXPLORE study also showed that many patients with recurrent attacks experience tiredness. Further assessments are needed to determine whether sleep disturbance is a critical domain to be measured when assessing QoL in AIP.…”
Section: Discussionmentioning
confidence: 72%
“…107 This may be of clinical relevance since AIP patients with biochemical activity apparently have abnormalities in circadian rhythms or levels of clock-controlled genes, including ALAS1. 108 In addition, dietary iron can control circadian gluconeogenesis in the liver via the regulation of haem synthesis. 109…”
Section: C Circadian Rhythmmentioning
confidence: 99%